Analisis Faktor-Faktor Pendapatan Kepala Rumah Tangga Miskin Pada Sektor Informal Di Kecamatan Abian Semal Kabupaten Badung - Wijaya, Gede Didiek; Djayastra, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2014)
Poor issue is main development challenge in the world including is Indonesia. The result of decreasing of proverty level that have been conducted for three decade in Indonesia is still suspectible with politic economic condition change, social conflict and natural disaster. Badung regency is regency have highest income in Bali province but have high unemployment level too. This study aims to find out the effect of the domestic head’s age, education level, working hour, family responsibility number, simultanously and partially toward the domectic head who working at informal sector in the subdistrict of Abiansemal, Badung. Number of sample were 81 respondents. The result showed that domestic head’s have positive and significant effect toward domestic head’ income, the third others that are education level, working hour, and family responsibility number have positive effect but not significant toward poor domestic head income at informal sector in the subdistrict of Abiansemal of Badung regency.
Keywords: Age; domestic head; education level; working hours; family responsibility number; income